Способи творення будівельно-інженерних термінів - Халілова, В. (СумДПУ ім. А. С. Макаренка, 2020)
The article introduces the reader to the formation of construction and engineering terminology by lexical-semantic, morphological and semantic methods. The purpose of the article – is to investigate the formation of construction and engineering terminology in different ways. The final part is about ways to form professional terms and highlight the intensive exchange of professional information.
Keywords: term; будівельно-інженерний термін; lexical-semantic method; лексико-семантичний спосіб; morphological method; морфологічний спосіб; semantic method; семантичний спосіб